Climate change and poverty A new agenda for developed nations - Fitzpatrick, Tony (Policy Press, 2014)
Climate change and poverty offers a timely new perspective on the 'ecosocial' understanding of the causes, symptoms and solutions to poverty and applies this to recent developments across a number of areas, including fuel poverty, food poverty, housing, transport and air pollution.